ChemInform Abstract: Rhodium‐Catalyzed Olefination of Aryl Tetrazoles via Direct C—H Bond Activation. Issue 12 (March 2015) - Wang, Liang; Wu, Wenting; Chen, Qun; He, Mingyang
Abstract A straightforward route for the synthesis of o‐alkenylaryl tetrazoles via Rh‐catalyzed C—H olefination of aryl tetrazoles is described.